System Models of Risk Management in the Formation of Programs of Innovative Development of the Region - M. K. Uandykova (Модернизация, инновация, развитие, 2019)
Purpose: the aim of the work is to study the risks of innovative development of regions and industries, develop systemic risk management models in the formation and implementation of innovative development programs in the region.Methods: the work used general scientific methods and approaches to research, such as analysis, comparison, generalization, optimization methods. Methodological approaches of risk management models include concepts, approaches aimed at the problems of risk management in the formation and implementation of regional innovative development programs, studied in domestic and foreign literature; mathematical apparatus of dichotomous and network programming.Results: the article provides a methodological justification and description of the criteria aspects of managing such tasks, risk analysis, develops a theory of project risks of a complex of innovative development programs for regions, presents models for assessing complex risk of a program, gives a statement of the problem of risk management and the formation of multi-purpose programs taking into account complex risks, as well as limitations for financing medium-risk and high-risk programs, algorithms for solving the risk management problem by dichotomous methods and networks are presented of programming. The transition from program-targeted management to integrated (joint system use of the project and scenario approaches) was completed, which allowed us to consider them holistically, form a complex of projects–programs, apply risk management mechanisms based on qualitative assessments and propose quantitative models for managing project and program risks of a program complex.Conclusions and Relevance: the proposed approach can be used in the formation and implementation of many program-targeted documents of the state and regional level with the transition to project management, as a tool for analysis and accounting of risks.